PENGELOLAAN KONFLIK DALAM ORGANISASI PENDIDIKAN DI SD NEGERI SUNGAI KITANO 1 KECAMATAN MARTAPURA TIMUR - Yuliansyah; Arisandi Tiya Rini; Fitriyadi Ramadhan; Siti Zubaidah; Trisna; Ahmad Suriansyah; Ratna Purwanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Conflict is an inevitable phenomenon within educational organizations, including at the elementary school level. This study aims to analyze the forms of conflict, causal factors, impacts, and conflict management strategies within the educational organization at SDN Sungai Kitano 1, East Martapura District. The study employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation. The findings indicate that the conflicts occurring are relatively minor and generally involve differences in perceptions, communication issues, and task distribution. The factors contributing to conflict include individual differences, ineffective communication, and demands arising from educational policies. The impact of conflict can be both positive and negative, depending on how it is managed. Conflict resolution strategies are implemented through open communication, deliberation, and a familial approach led by the school principal. These findings highlight that effective conflict management can foster a harmonious work environment and support the improvement of educational quality.